Deep longitudinal multi-omics analysis of Bordetella pertussis cultivated in bioreactors highlights medium starvations and transitory metabolisms, associated to vaccine antigen biosynthesis variations and global virulence regulation - Anziani, Paul; Becker, Jérémie; Mignon, Charlotte; Arnaud-Barbe, Nadège; Courtois, Virginie; Izac, Marie; Pizzato, Romain; Abi-Ghanem, Joséphine; Tran, Viet-Dung; Sarafian, Magali; Bunescu, Andrei; Garnier, Dominique; et al. (Frontiers in Microbiology, 2023)
Bordetella pertussis is the bacterial causative agent of whooping cough, a serious respiratory illness. An extensive knowledge on its virulence regulation and metabolism is a key factor to ensure pertussis vaccine manufacturing process robustness. The aim of this study was to refine our comprehension of B. pertussis physiology along the fermentation process. A longitudinal multi-omics analysis was carried out over a 26-hour small-scale fermentation of B. pertussis. Fermentations were performed in batch mode and under culture conditions intending to mimic industrial processes. Putative cysteine and proline starvations were respectively observed at the beginning of the exponential phase (from 4h to 8h) and during the exponential phase (18h45). As revealed by multi-omics analyses, the proline starvation induced major molecular changes, including a transient metabolism with internal stock consumption. In the meantime, growth and specific total PT, PRN and Fim2 antigen productions were negatively affected. Interestingly, the master virulence-regulating two-component system of B. pertussis (BvgASR) was not evidenced as the sole virulence regulator in this in vitro growth condition. Indeed, novel intermediate regulators were identified as putatively involved in the expression of some virulence-activated genes (vags). Such longitudinal multi-omics analysis applied to B. pertussis fermentation process emerges as a powerful tool for characterization and incremental optimization of vaccine antigen production.